2023
DOI: 10.35754/0234-5730-2023-68-2-219-228
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in patients with congenital bleeding disorders in Russia

Abstract: Background. Internationally published data about the course of COVID-19 in patients with congenital bleeding disorders (CBDs) are limited. There are questions about how COVID-19 affects the course of CBDs and, conversely, how CBDs affect the course of coronavirus infection.Aim — to analyze the course of COVID-19 in patients with CBDs in Russia.Materials and methods. A cross-sectional survey was conducted at the National Medical Research Center for Hematology (Moscow) for the period from June 25 to July 31, 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…However, information about the severity of hemophilia A was not available in seven studies ( n = 4,232; 93.7%). 14 15 16 18 19 20 21 Out of 4,517 patients with hemophilia A, an inhibitor was observed in 29 patients (0.6%) across four studies. 7 8 12 14 However, information about inhibitors in hemophilia were not provided in eight studies ( n = 4,029; ∼89%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, information about the severity of hemophilia A was not available in seven studies ( n = 4,232; 93.7%). 14 15 16 18 19 20 21 Out of 4,517 patients with hemophilia A, an inhibitor was observed in 29 patients (0.6%) across four studies. 7 8 12 14 However, information about inhibitors in hemophilia were not provided in eight studies ( n = 4,029; ∼89%).…”
Section: Resultsmentioning
confidence: 99%
“…12 In addition, it was reported that two patients (<1%) had factor XIII (FXIII) deficiency, 7 13 while five patients (<1%) each were reported to have FVII deficiency and FX deficiency. 12 18 20 21 FV deficiency was reported in two patients (<1%), and congenital fibrinogen disorder and FXI deficiency were reported in one patient each (<1%). 13 20 Three studies did not differentiate between the types of RBD ( n = 13; 0.1%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations